Adherence to needlestick injury presentation guidelines among staff nurses and student nurses in Manila - Delos Santos, Jose Raphael M.; Derije, Heather Marie U.; Descalzo, Andrea Franchesca D.C; Galliguez, Greigh E.; Galutan, Chelsea Joy M.; Go, Marion Carla A.; Poltic, Ner Foxworth V.; Tonson, Frenchesca Clerence Denise G.
Needlestick injury (NSI) is still a major health concern in the healthcare system due to its high incidence rate, especially among the nurses who acquire the most number due to their frequent handling of needles, despite presence of guidelines and protocols. Recognizing that adherence is multifactorial, researchers have only focused on the relationship of education and knowledge of nurses to their adherence, which showed an inverse relationship, implying significant difference in the level of adherence between staff and student nurses. This study aims to determine the gaps or differences to needlestick injury prevention guidelines (NSIPG) between staff nurses and student nurses and its association with the different variables affecting it. A descriptive correlational design was used. A total of 104 staff nurses from two (2) level III hospitals and 258 student nurses from schools affiliated to these hospitals participated. A self-administered questionnaire was used to determine the respondents’ perceptions on the severity and their susceptibility to NSIs, and their perceived barriers and benefits from NSI prevention. The head or charge nurses in each hospital ward were also interviewed to provide reliable information for the organizational characteristics that can influence the staff nurses’ and student nurses’ adherence to NSIPG.